An Analysis of Da'wah Education Verses in Tafsir Ayat Al-Ahkam (Rawai'ul Bayan) Chapter 10 by Muhammad Ali Ash-Shabuni - Mashuri Mashuri; Sarbini Anim; Siti Nuri Nurhaidah (Global Education Journal, 2026)
Da'wah education is a fundamental aspect of shaping Islamic character and strengthening religious understanding among Muslims, particularly amid social dynamics that demand precise, humane, and contextual methods of conveying Islamic teachings. However, academic studies that specifically examine the educational dimension of da'wah within contemporary works of tafsir ahkam, particularly Rawai'ul Bayan by Muhammad Ali Ash-Shabuni, remain relatively limited, despite the fact that the book is widely recognized as a principal reference for the study of legal verses, systematically combining linguistic, jurisprudential, and comparative (tarjih) approaches. This study aims to analyze the values of da'wah education contained in the verses discussed in Chapter 10 of Rawai'ul Bayan and to identify the relevance of Ash-Shabuni's exegetical method for the development of contemporary da'wah education. This research employs a qualitative approach through library research. Primary data were obtained from the text of Rawai'ul Bayan, while secondary data were drawn from relevant and up-to-date scholarly journals, books, and articles. Data were analyzed using content analysis combined with a thematic (maudhui) exegetical approach. The findings show that the verses in Chapter 10 of Rawai'ul Bayan embody three pillars of da'wah education: al-hikmah (argumentative wisdom), mau'izah hasanah (heartfelt good counsel), and mujadalah bi allati hiya ahsan (constructive dialogue), all of which are oriented toward the gradual and humane formation of religious understanding. This study recommends that Ash-Shabuni's exegetical method be adopted as a reference in developing more adaptive models of da'wah education responsive to the needs of contemporary society.